Mechanical, physical properties and tribological behaviour of silicon carbide composites with addition of carbon nanotubes. (June 2019) - Džunda, Róbert; Fides, Martin; Hnatko, Miroslav; Hvizdoš, Pavol; Múdra, Erika; Medveď, Dávid; Kovalčíková, Alexandra; Milkovič, Ondrej
Abstract: Four types of silicon carbide/carbon nanotubes composites were prepared with the main aim to develop ceramics with enhanced electrical conductivity. The SiC/CNT composites were prepared by in-situ growth of CNT on the SiC powder grains. Three types of SiC/CNT composites, where the precursor SiC/CNT powder mixture was prepared by Catalytic Chemical Vapour Deposition (CCVD) method and different amounts of Fe catalytic nanoparticles (2.5, 5, 10 wt% Fe), were designed. In addition, one reference material containing 2.5 wt% Fe catalytic nanoparticles but without CCVD application, i.e. without CNT, was prepared in order to correctly assess the role of CNT. The experimental materials were compacted by hot pressing (1850 °C/Ar/60 min/40 MPa). Mechanical properties such as hardness and elastic modulus of experimental materials were determined. Electrical conductivity as a function of CNT content was measured. The effect of the CNT addition on tribological properties (coefficient of friction, wear) of SiC/CNT composites was also observed. Hardness of the reference sample was relatively high (HV1 = 24 GPa) and it decreased down to HV1 = 17–19.8 GPa with presence of CNT. Similarly, the fracture toughness decreased with presence of CNT from 4.99 MPa.m 1/2 for the reference sample down to 3.4–4 MPa.m 1/2 for the SiC/CNT composites. Nanoindentation showed that hardness HIT of reference sample without CNT was around 26 GPa and with increasing amounts of CNT it decreased down to 21 GPa. The composites had similar modulus of elasticity (EIT  = 337–348 GPa), while for the reference sample it was EIT  = 434 GPa. Electrical conductivity increased with amount of CNT (1.76 S/m for the reference sample, 484.3 S/m for the composite with 2.5 wt% Fe, and up to 2873.6 S/m for the composite with 10 wt% Fe). Specific wear rate increased with presence of CNT from 7.7 × 10 −7  mm 3 /Nm for the reference sample to 2.4–2.9 × 10 −6  mm 3 /Nm for the composites. Complex wear behavior common for all types of experimental materials was observed: mainly abrasion, mechanical wear (micro-fractures) and tribochemical reactions with created SiO2 layer. In the reference sample the dominant wear mechanism was abrasion, in SiC/CNT composites formation of transferred films in wear tracks consisting of oxides and carbon phases formed by crushing the CNT were observed. Highlights: Dense SiC/CNT composites were prepared by CCVD process. The electrical conductivity increased by 3 orders of magnitude. The highest benefit was the improvement of the electrical conductivity for proper electrical discharge machining.